The interactive effects of emotions and numerical information in increasing consumer support to conservation efforts - Felix Septianto; Joya A.Kemper; Chiew, Tung Moi (Elsevier, 2020)
Nearly 50% of all Earths’ forests have been cleared and considering forests hold 80% of the world’s diversity, it is crucial to support efforts by non-profit organizations (NPO) and government to stop deforestation. Yet, NPOs combat in an increasingly competitive donation sphere, with only 3% of donations going to conservation and animal welfare NPO’s. The present research aims to develop a novel perspective to increase consumer support (financial and time resources) to NPOs by examining the use of emotion (hope vs. fear) and numerical information (range vs. point value). Across three experimental studies, we provide concrete empirical evidence that hope increases the effectiveness of numerical information specified as a point value format, whereas fear will increase the effectiveness of numerical information specified as a range format. Our results provide practical implications for conservation NPO marketers in terms of matching emotion and numerical format.